Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1997
DOI: 10.7863/jum.1997.16.12.813
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamic changes in the early phase of artificially created arteriovenous fistula: color Doppler ultrasonographic findings.

Abstract: The objective of this study was to evaluate hemodynamic variables in arteriovenous fistulas by color Doppler ultrasonography. This study involved 28 patients with chronic renal failure who were sent to surgery clinic for creation of an arteriovenous fistula of the Brescia-Cimino type. Patients were evaluated preoperatively and on the first and seventh days postoperatively by a color Doppler ultrasound machine with a 7.5 MHz linear probe. The distal radial artery was examined preoperatively and the fistula itse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 4 publications
(2 reference statements)
0
10
0
Order By: Relevance
“…This trend was similar to those reported in previous studies. [6,8] However, our follow-up was extended to 6 months, and we observed that the native radiocephalic fistula continued to mature until the last follow-up examination. Some authors recommend the early use of arteriovenous fistulae, [4,5] but the K/DOQI guideline recommends that new arteriovenous fistula be punctured after a period of at least 1 but preferably 3 to 4 months.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…This trend was similar to those reported in previous studies. [6,8] However, our follow-up was extended to 6 months, and we observed that the native radiocephalic fistula continued to mature until the last follow-up examination. Some authors recommend the early use of arteriovenous fistulae, [4,5] but the K/DOQI guideline recommends that new arteriovenous fistula be punctured after a period of at least 1 but preferably 3 to 4 months.…”
Section: Discussionmentioning
confidence: 86%
“…[4] However, few studies with limited follow-up times had examined the course of AVF maturation. [6][7][8][9] The aim of this prospective study is to evaluate the natural course of AVF maturation using Doppler ultrasound and examine the factors that can affect AVF maturation.…”
Section: Introductionmentioning
confidence: 99%
“…1,3,4 Although many of those studies examined both arteries and veins, none has shed light on the comparison of success rates between the intraoperative thrill noted by the surgeons and the CDUS findings. Mahmutyazicioglu and colleagues 5 have documented a study in which CDUS was used in evaluating the postoperative hemodynamic changes in the RA. Malovrh 1 reported on the preoperative assessment of the internal diameter and the Doppler flow signals in the RA by duplex sonography.…”
Section: Discussionmentioning
confidence: 99%
“…Connecting a high-pressure artery to a low-pressure vein often causes arterial and venous dilation and substantially increased blood flow in the new circuit. Early AVF development by using ultrasonographic (US) diameter and flow measurements has only been described in small, singlecenter studies (1)(2)(3)(4). Publications have focused on forearm AVF, with relatively little quantitative data reported on upper-arm AVFs, a common site of AVF placement in the United States.…”
mentioning
confidence: 99%